2010
DOI: 10.1021/np100492j
|View full text |Cite
|
Sign up to set email alerts
|

Pyridone and Tetramic Acid Alkaloids from the Spider Pathogenic Fungus Torrubiella sp. BCC 2165

Abstract: Torrubiellones A-D (1-4), new pyridone and tetramic acid alkaloids, were isolated from the spider pathogenic fungus Torrubiella sp. BCC 2165. Torrubiellone A (1) exhibited antimalarial activity with an IC(50) value of 8.1 μM, while it showed very weak cytotoxic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…Their distinctive nutritional requirements for particular metabolites lead to specific host preferences. Recent studies of these fungi have been focused on bioactive compounds with fungistatic and bacteriostatic activities (Wipapat et al 1998;Lee et al 2005;Kuephadungphan et al 2013;Bunbamrung et al 2015), as well as new compounds including cyclic tetrapeptides (Lang et al 2005), ergosterols and isariotin analogs (Asia et al 2012), and alkaloids (Isaka et al 2010(Isaka et al , 2013. Biocompatible polymers have received particular attention (Madla et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Their distinctive nutritional requirements for particular metabolites lead to specific host preferences. Recent studies of these fungi have been focused on bioactive compounds with fungistatic and bacteriostatic activities (Wipapat et al 1998;Lee et al 2005;Kuephadungphan et al 2013;Bunbamrung et al 2015), as well as new compounds including cyclic tetrapeptides (Lang et al 2005), ergosterols and isariotin analogs (Asia et al 2012), and alkaloids (Isaka et al 2010(Isaka et al , 2013. Biocompatible polymers have received particular attention (Madla et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…12 Hybrid PKS-NRPS genes are widespread in fungi. 7,1315 We expect that recently published genome sequence data 16 will facilitate identification of hybrid synthetases in M. acridum and that a functional analysis using a gene knockout approach will identify the gene responsible for the metacridamide biosynthetic pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular formula of torrubiellin B (2) was determined by HRESIMS as C 30 H 20 O 10 , which has two more oxygen atoms than 1. The 1 H and 13 C NMR spectra suggested close structural resemblance to 1, although the 1 H NMR spectrum of 2 in DMSO-d 6 (used due to the solubility reason) did not exhibit any peaks for phenolic OH. Interpretation of the 2D NMR (COSY, HMQC and HMBC) data revealed that the BCDEFG-ring structure was identical to 1.…”
Section: Introductionmentioning
confidence: 92%
“…Two scale insect pathogenic species, Conoideocrella luteorostrata (formerly T. luteorostrata) and C. tenuis (formerly T. tenuis) have recently been investigated as sources of novel bioactive compounds, such as paecilodepsipeptides 2 and conoideocrellides 3 (hexadepsipeptides), luteorides 4 (prenylated tryptophan analogs), isocoumarin glucosides, 3,5 bioxanthracenes, 3 and hopane-type triterpenes. 3 In contrast, there has been only one report on bioactive compounds from the spider-pathogenic Torrubiella, torrubiellones A-D (pyridone and tetramic acid derivatives), 6 and no report on leafhopper pathogens. As part of our research program on novel bioactive compounds from arthropod-pathogenic fungi, we selected a leafhopper-pathogenic Torrubiella sp., strain BCC 28517, for large-scale fermentation and chemical studies.…”
Section: Introductionmentioning
confidence: 99%